Engineering mechanics - Sawhney, G.S (PHI Learning, 2010)
The book presents succinct coverage of the theory, definitions and formulae. It is well supported by plenty of clear-cut diagrams, suitable examples and worked problems in order to make the underlying principles comprehensive.